STUDI ANALISIS KETELITIAN GEOMETRIK HORIZONTAL CITRA SATELIT RESOLUSI TINGGI SEBAGAI PETA DASAR RDTR PESISIR (STUDI KASUS: KECAMATAN BULAK, SURABAYA) - Sukojo, Bangun Muljo; Alawy, Moh. Mahfudhdin (GEOID, 2016)
The availability various of high resolution satellite imagery with high accuracy at less than one meter, show that remote sensing technology is developed, that impact on the increased accuracy of various base maps that require a high scale example of at least 1: 5000 in the preparation of base maps a detailed plan to spatial structure of urban, industrial and coastal which will be reviewed in this study. Of course, to meet the high scale, high-resolution satellite images must be processed and corrected to minimize Geometrik errors. The data that is used in this study is the high-resolution satellite Pleiades 1B imagery in 2015 data acquisition and Geoeye in 2013. Each imagery data carried out Geometrik correction process that is carried out using the Affine and Polynomial Order 2 transformation method. As the supporting data is Ground Control Points (GCP) data as much as 9 points and 23 Independent Check Points (ICP), all of the Control Point is measured using GPS Geodetik and also 21 planimetric distance measurement data, this data is used for Geometrik correction process until the Geometrik accuracy tests performed on each image. In the end the results of this study showed that each of image that has performed Geometrik correction have the results of the accuracy that meets the standards of accuracy base map up to a scale of 1: 5000 in Class 1, with details of the correction process Geometrik rectification generate the RMS Error indicating that the Polynomial Order 2 method on the image of the Pleiades 1B 0,158 and GeoEye 0,089 have RMS Error values are better than the Affine method on Pleides 1B and GeoEye that have result of 0,253 and 0,173, horizontal Geometrik accuracy CE90 Geoeye satellite imagery with a value of 0,697 better than the Pleiades 1B that has a value of 0 , 731. as well as on the planimetric accuracy test showed GeoEye imagery with a value of 0,506 accuracy better than Pleiades 1B at 0,648.ye imagery with a value of 0,506 accuracy better than Pleiades 1B at 0,648.